The Health Ritual of "Pag-aanito" among the Aetas of Nabuclod, Pampanga, Philippines - Rudolf Cymorr Kirby Martinez (San Beda University, 2019)
A defining characteristic of an indigenous group is that it has preserved its unique traditional ways of living, belief system or pertinent rituals amidst the presence of modernity. One of the indigenous group residing in the Philippines are the Aeta people, found scattered in the archipelago. One of the unique cultural health beliefs of this indigenous group revolves around the spirit called "anito" and the ritual for appeasing this spirit termed as "pag-aanito." This paper explores the contemporary understanding of a select group of Aeta from Pampanga, Philippines on these unique cultural health beliefs and how their understanding and appreciation of their traditional customs affects their perception of the world, themselves, and their health.